Hubungan Shift Kerja Dengan Kualitas Tidur Perawat Ranap Inap di RSUP dr. Sitanala Tangerang - Amelia Mustika Dewayanti, (2020)
Sleep quality is very important because it can make health better and can cause high concentrations, sleep quality can also have a very big influence on work shifts.Work shift that is not well scheduled will have an impact on the quality of nurse sleep. This study aims to analyze the relationship of work shifts with the sleep quality of the inpatient nurses in RSUP dr. Sitanala Tangerang, this type of research is a descriptive analytic study with cross sectional approach and analyzed by Chi-Square Test, the population in this study is inpatient nurses at RSUP dr. Sitanala Tangerang, a sample of 57 people, sampling using a total sampling technique, the research results found there is a relationship of work shifts with the sleep quality of inpatients nurses at RSUP dr. Sitanala Tangerang (p = 0.001). This research can provide input for the nursing profession in raising awareness of the importance of sleep time after completing work shifts.